Clinicopathological significance of laminin‐5γ2 chain expression in superficial esophageal cancer. Issue 5 (14th September 2012) - Ito, E.; Ozawa, S.; Kijima, H.; Kazuno, A.; Miyako, H.; Nishi, T.; Chino, O.; Shimada, H.; Tanaka, M.; Inoue, S.; Inokuchi, S.; Makuuchi, H.
Summary The glycoprotein laminin 5γ2 chain (LN‐5γ2) has recently become a focus of increased interest and investigation as a marker of invasion in gastrointestinal malignancies. We investigated the significance of LN‐5γ2 expression as a prognostic factor in superficial esophageal cancer. The study population consisted of 87 patients who had undergone a transthoracic esophagectomy and three‐field lymphadenectomy for the treatment of superficial esophageal cancer at Tokai University Hospital. Formalin‐fixed, paraffin‐embedded sections of the resected specimens were examined using immunohistochemical staining and hematoxylin and eosin staining to assess the correlations between the LN‐5γ2 expression pattern and the clinicopathological factors (age, sex, T‐factor, N‐factor, ly‐factor, v‐factor, degree of differentiation, infiltrative growth pattern, tumor node metastasis classification of malignant tumors [TNM] stage, etc.) and the patient outcome. The expression pattern of LN‐5γ2 was classified into an extracellular type (E type), characterized by the staining of extracellular matrix such as the basement membrane and the stroma (31 cases, 35.6%), and a cytoplasmic type (C type), characterized by the staining of the cytoplasm in the cancer cells (56 cases, 64.6%). The expression pattern was not correlated with any of the clinicopathological factors that were assessed. However, univariate analyses of the survival analysis data showed that the N‐factor (P = 0.011), TNM stage (P = 0.011), and LN‐5γ2 C type (P = 0.017) were prognostic factors. A multivariate analysis revealed that the N‐factor (P = 0.049) and LN‐5γ2 C type (P = 0.048) were prognostic factors. In the survival analysis, a univariate analysis of the 75 T1b cases also showed that the N‐factor (P = 0.048), TNM stage (P = 0.048), and LN‐5γ2 C type (P = 0.029) were prognostic factors, while a multivariate analysis showed that the LN‐5γ2 C type (P = 0.035) was a prognostic factor. The C type expression of LN‐5γ2, i.e. confined to the cytoplasm, was correlated with an unfavorable outcome among the patients with superficial esophageal cancer in the present series. Observation of the LN‐5γ2 expression pattern may be useful for the diagnosis of highly malignant tumors.